2019
DOI: 10.3389/fimmu.2019.01775
|View full text |Cite
|
Sign up to set email alerts
|

The BtaF Adhesin Is Necessary for Full Virulence During Respiratory Infection by Brucella suis and Is a Novel Immunogen for Nasal Vaccination Against Brucella Infection

Abstract: Brucella enters their hosts mostly through mucosae from where it spreads systemically. Adhesion to extracellular matrix (ECM) components or to host cells is important for the infectious process, and is mediated by several adhesins, including the BtaF trimeric autotransporter. Although Th1 responses and gamma interferon (IFN-γ) are important for protection, antibodies able to block adhesions might also contribute to prevent Brucella infection. We evaluated the importance of Bta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 66 publications
1
22
0
3
Order By: Relevance
“…Brucella infection is frequently acquired through the oral and respiratory routes, and adhesins are anticipated to have a relevant role in these infectious processes. As mentioned above, our results showed that BtaF adhesin from B. suis is necessary for complete virulence of B. suis after both oral and intratracheal infection [ 70 , 71 ]. In line with these results, we assessed the immunogenic and protective potential of recombinant BtaF when administered intranasally with the mucosal adjuvant Bis-(3’,5’)-cyclic dimeric adenosine monophosphate (c-di-AMP) [ 71 ].…”
Section: Adhesins Of Brucellamentioning
confidence: 95%
See 1 more Smart Citation
“…Brucella infection is frequently acquired through the oral and respiratory routes, and adhesins are anticipated to have a relevant role in these infectious processes. As mentioned above, our results showed that BtaF adhesin from B. suis is necessary for complete virulence of B. suis after both oral and intratracheal infection [ 70 , 71 ]. In line with these results, we assessed the immunogenic and protective potential of recombinant BtaF when administered intranasally with the mucosal adjuvant Bis-(3’,5’)-cyclic dimeric adenosine monophosphate (c-di-AMP) [ 71 ].…”
Section: Adhesins Of Brucellamentioning
confidence: 95%
“…An indirect ELISA assay on sera from healthy and sick pigs infected with B. suis suggested that both adhesins are expressed in vivo in the natural host (swine), supporting the role of these adhesins in the infection process. Recently, it was shown that BtaF is also required for virulence in mice after inoculation via a respiratory (intratracheal administration) route [ 71 ]. In this case, the splenic load of the deletion mutant was significantly reduced at 7-days and 30-days post-infection as compared to the wild-type strain.…”
Section: Adhesins Of Brucellamentioning
confidence: 99%
“…The literature shows that the reduction in mouse spleen colonization has been reported previously for several B. suis vaccine candidates. Nasal immunization with a recombinant adhesin (BtaF) in cyclic-di-AMP protected mice against B. suis bv1 administered intragastrically but not when challenged intratracheally [ 61 ]. However, the protocol of immunization and costs indicate that this vaccine when improved with BtaF synergic antigens [ 61 ] would be more suitable for human use.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal immunization with a recombinant adhesin (BtaF) in cyclic-di-AMP protected mice against B. suis bv1 administered intragastrically but not when challenged intratracheally [ 61 ]. However, the protocol of immunization and costs indicate that this vaccine when improved with BtaF synergic antigens [ 61 ] would be more suitable for human use. Strain VTRS1, an R wboA mutant of B. suis biovar 4 [ 22 ], when administered intravenously (IV), was more efficacious against B. suis bv4 than RB51 administered IP.…”
Section: Discussionmentioning
confidence: 99%
“…The Brucella suis trimeric autotransporter F (BtaF) and E (BtaE) are described as a promising immunogenic target for vaccination against mucosal B. suis infections [242]. Other research concerning the vaccine development targeting melioidosis and glanders caused by Burkholderia pseudomallei and Burkholderia mallei, respectively, is ongoing and describes various expressed TAAs with immunogenic properties such as BPSL2063 [243] and BimA [244,245].…”
Section: Other Taasmentioning
confidence: 99%